Охранные исследования Альминской экспедиции в 2008 г. - Пуздровский, А.Е.; Медведев, Г.В.; Соломоненко, А.Е.; Труфанов, А.А. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the protective research of Ust-Alma Late Scythian necropolis (Pishchane village), of an ancient cistern at Vilino settlement in Bakhchisaray Region of the Crimea, and of Bus Station settlement in Simferopol.